Optimization of thin layers of coated turmeric extract (Curcuma longa L) tablets using a dipping method - Permadi, Adi; Yuliani, Sapto; Wahyuningsih, Iis; Satar, Ibdal (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Turmeric extracts have many benefits, such as an anti-oxidant, anti-inflammatory, and neuro-protector for dementia. The turmeric extracts can be prepared in the form of a thin layer of coated tablets through a dipping method using the dip coating and Simplex lattice design (SLD) methods. The quality of the thin layers of coated tablets is much related to the formulation in the coating process. This research aims to formulate and optimize the coating composition of HPMC, PEG-400, and dip time. Consequently, the TSLT meets the standard requirements. The core tablets were made by using the wet granulation method with the formulation of turmeric extract, erosol, lactose, gelatin, and aquades. Before the core tablets had been produced, the eligibility of granules was initially evaluated based on the standard requirements. Subsequently, the core tablets that meet the standard requirements were printed and replicated. The coating processes on core tablets were performed by dipping into the coating solution in the various duration of dipping times: 5, 30, and 60 seconds. The coating solution consists of HPMC, PEG-400, glycerine, sunset yellow, and distillate water. Then, produced TSLTs were evaluated based on the hardness, friability, and disintegration time. The best optimization process for the mixture of HPMC and PEG-400 indicates a more positive value of R (R = 0.2024).